Gas coning in oil wells - Saleh, Talib (Iraqi Journal of Science, 2023)
Gas coning is one of the most serious problems in oil wells. Gas will reach the perforations and be produced with oil. Anyhow there is a certain production rate called critical production rate. The daily production rate should not exceed the critical production rate. In this research ten oil wells have been tested for problem of gas coning for a period of time of eighteen months. The production rates of these Ten oil wells are tabulated in a table exist in this research.These production rates are considered as critical production rate because no gas coning has been observed in these wells. The critical production rates of these wells don’t concide with those obtained from (Meyer, Gardiner, Pirson) method and also they don’t concide with the values calculated by Albert Lewis (a.l).An empirical equation was found which represents the actual production rates exactly.Errors percentage in the calculations by using (Meyer, Gadiner and Pirson ) method and also by using Albert Lewis (a.l) method are shown in table exist in this research.